The Role of female principals of school in Enhancing Information Security at the Secondary Level in Al-Kharj Governorate - Al-Mosa, Suha Fahad (Journal of Educational and Psychological Sciences, 2025)
The study aimed to determine the role of school principals in enhancing information security at the secondary level in Al-Kharj Governorate, according to the dimensions (confidentiality of information, integrity of information, and abundance of information), and to determine the extent to which there are statistically significant differences according to the variables (job title- number of years of experience). The study followed the descriptive survey method, and a questionnaire was distributed to a stratified sample of (626) managers and agents. The study found that the role of school principals in enhancing information security at the secondary level in Al-Kharj Governorate came with a mean of (4.20 out of 5), with a degree of (high), and the dimensions were in descending order: confidentiality of information and an average of (4.23), with a degree of (very high). Then integrity of information with an average of (4.20), and third: abundance of information with an average of (4.16). Both of them were (high), and the results of the study showed that there were statistically significant differences attributed to the job title variable in favor of female principals, while there were no statistically significant differences attributed to the years of experience variable. Based on the results, the researcher recommended the need to strengthen the role of school principals in information security by complying with regulations. Security of the information contained in the usage and privacy policy, by activating the password update periodically, Training school employees on the latest technology in the field of computers, and educating school principals about information security policies and procedures. In light of the results of the study and its recommendations, it is proposed to conduct studies related to the role of school principals in managing security crises in light of digital transformation, or the reality of school employees’ awareness of information security in educational institutions.
Keywords: Role; opinions of female directors; information security; electronic administration; Al-Kharj Governorate